1994
DOI: 10.1159/000288888
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors and Vulnerability to Psychiatric Morbidity after Myocardial Infarction

Abstract: A sample of 97 males suffering from myocardial infarction was studied in order to determine the influence of psychological variables and emotional states on psychopathology displayed by patients in the course of their cardiological recovery. Discriminant analysis revealed that depression in the coronary unit and nonuse of problem-solving strategies were the most sensitive variables to correctly classify psychiatric and nonpsychiatric cases (76.6% of the total sample). Multiple regression analysis of the psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…A total of 18 studies, including the 4 above, reported prevalence data 1 month or longer after AMI without necessarily distinguishing persistent depression from new incidence and remission patterns. Of the 18 studies, 7 employed commonly used standardized clinical interviews for the diagnosis of depression, 33,36,44,49–52 11 used validated questionnaires or rating scales such as the BDI, 39,40,42,44,47 the Zung Depression Rating Scale (ZDS), 55,57 the HADS, 26,28 the SCL‐90 Depression Subscale, 54 or the Depression Scale, 56 and one used Goldberg's Clinical Interview Schedule 53 (Table 3). The studies varied widely in terms of method and timing of assessment and reported prevalence rates.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 studies, including the 4 above, reported prevalence data 1 month or longer after AMI without necessarily distinguishing persistent depression from new incidence and remission patterns. Of the 18 studies, 7 employed commonly used standardized clinical interviews for the diagnosis of depression, 33,36,44,49–52 11 used validated questionnaires or rating scales such as the BDI, 39,40,42,44,47 the Zung Depression Rating Scale (ZDS), 55,57 the HADS, 26,28 the SCL‐90 Depression Subscale, 54 or the Depression Scale, 56 and one used Goldberg's Clinical Interview Schedule 53 (Table 3). The studies varied widely in terms of method and timing of assessment and reported prevalence rates.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 It has also been useful in creating and informing new behavioral therapies such as ''behavioral cardiology'' that seek to reduce the patient's risk for negative health outcomes by improving their ability to cope with stressful emotions and challenges. Now in the third-edition, Problem-Solving Therapy lays out a positive psychology and stress and coping approach to enhance adaptive coping as a way to avert exacerbations in chronic diseases.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] In addition, depression is common in the postinfarction period and is a welldocumented predictor of absenteeism, disability, and poor health-related quality of life. [8][9][10][11][12][13][14] An estimated 50-90% of people who worked before a myocardial infarction return to work after recovery. [15][16][17][18][19][20][21][22][23][24] It is therefore important to assess the effects of a myocardial infarction and any residual physical or mental influences on work performance and attendance rates.…”
mentioning
confidence: 99%